Transforming Growth Factor-Beta (TGF-β) Signaling in Cancer-A Betrayal Within - Baba, Abdul Basit; Rah, Bilal; Bhat, Gh. Rasool; Mushtaq, Ifra; Parveen, Sabra; Hassan, Rukhsana; Hameed Zargar, Mahrukh; Afroze, Dil (Frontiers in Pharmacology, 2022)
A ubiquitously expressed cytokine, transforming growth factor-beta (TGF-β) plays a significant role in various ongoing cellular mechanisms. The gain or loss-of-function of TGF-β and its downstream mediators could lead to a plethora of diseases includes tumorigenesis. Specifically, at the early onset of malignancy TGF-β act as a tumor suppressor and plays a key role in clearing malignant cells by reducing cellular proliferation and differentiation thus triggers the process of apoptosis. Subsequently, TGF-β at an advanced stage of malignancy promotes tumorigenesis by augmenting cellular transformation, epithelial-mesenchymal-transition (EMT), invasion, and metastasis. Besides playing the dual roles, depending upon the stage of malignancy, TGF-β also regulates cell fate through immune and stroma components. This oscillatory role of TGF-β to fight against cancer or act as a traitor to collaborate and crosstalk with other tumorigenic signaling pathways and its betrayal within the cell depends upon the cellular context. Therefore, the current review highlights and understands the dual role of TGF-β under different cellular conditions and its crosstalk with other signaling pathways in modulating cell fate.